2022
DOI: 10.1039/d2cp02987a
|View full text |Cite
|
Sign up to set email alerts
|

Polaron formation and transport in Bi2WO6 studied by DFT+U and hybrid PBE0 functional approaches

Abstract: Bi2WO6 (BWO) is considered as a promising material for photocatalytic water splitting. It is unique layered structure leads the charge separation and transport is different from other materials. However, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…Consistent with the aforementioned materials, using DFT+U, the electron will form a small polaron on a single W site. In Bi 2 WO 6 , the electron polaron behavior is similar as that in WO 3 reported by Tao et al 10 When small electron polarons form in HfO 2 , 39 Ta 2 O 5 , 43 NaTaO 3 , 43 WO 3 and Bi 2 WO 6 using the DFT+U approach, the formation energies are all around À0.2 eV, which indicates a stable polaron state. However, when 2D polarons form, the formation energies are around À0.05 eV, indicating that the geometric distortion to form the 2D-like polaron is much smaller than when forming the localized small polarons.…”
Section: Polaron Formation In Materials With Cations Having 6s Electronssupporting
confidence: 81%
See 2 more Smart Citations
“…Consistent with the aforementioned materials, using DFT+U, the electron will form a small polaron on a single W site. In Bi 2 WO 6 , the electron polaron behavior is similar as that in WO 3 reported by Tao et al 10 When small electron polarons form in HfO 2 , 39 Ta 2 O 5 , 43 NaTaO 3 , 43 WO 3 and Bi 2 WO 6 using the DFT+U approach, the formation energies are all around À0.2 eV, which indicates a stable polaron state. However, when 2D polarons form, the formation energies are around À0.05 eV, indicating that the geometric distortion to form the 2D-like polaron is much smaller than when forming the localized small polarons.…”
Section: Polaron Formation In Materials With Cations Having 6s Electronssupporting
confidence: 81%
“…However, when using the hybrid functional, the hole will localize on a BiO 8 dodecahedron with Bi 6s and O 2p states, as reported by Kweon, Hwang, and Liu et al [7][8][9] The last example is the electron polaron in W-based materials. Tao et al 10 studied the formation of electron polarons in WO 3 and Bi 2 WO 6 (BWO) using DFT+U and hybrid PBE0 functional approaches. They found that the electron will form a small polaron on a single W stie using the DFT+U approach with U added to the W 5d state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the CBM, the contribution of W 6s orbital is usually ignored. However, in our previous paper, we demonstrated that it has an important role in charge carriers localized to small polarons. s orbitals are delocalized in nature and small polarons are localized in nature, which could be the reason for the observation of a 2D-shaped polaron in experiment.…”
Section: Resultsmentioning
confidence: 88%
“…Moreover, it is found that the 2D large polarons are critical for maintaining the structural stability of O′-MoO 3−x . Our results contribute to the basic understanding of the better performance for the carrier mobility and Li and H storage in reduced MoO 3 3,40,41 and provide a reference for optimizing the physical and chemical properties of molybdenum oxides in real applications, e.g., FET, pseudocapacitors, superconductors, 34…”
mentioning
confidence: 75%